(a+b)(a-b)+((b+c)(b-c)+(c+a)(c-a) simplify
Answers
Answered by
0
Answer:
a²-b²+b²-c²+c²-a²=0(by cancellation) mark me as the brainliest
Answered by
0
Answer:
(a+b)(a-b)+(b+c)(b-c)+(c+a)(c-a),
=(a²-b²)+(b²-c²)+(c²-a²),
=(a²-b²+b²-c²+c²-a²),
In this case, each variable cancels it's negative version.
= 0
NOW, THAT'S THE CORRECT ANSWER.
Similar questions
Math,
2 months ago
Social Sciences,
2 months ago
Math,
2 months ago
Computer Science,
4 months ago
Accountancy,
11 months ago
Math,
11 months ago
Biology,
11 months ago